2019
DOI: 10.3389/fvets.2019.00069
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Review of Equine SIRS, Sepsis, and Neutrophils

Abstract: The most recent definition of sepsis in human medicine can be summarized as organ dysfunction caused by a dysregulated host response to infection. In equine medicine, although no consensus definition is available, sepsis is commonly described as a dysregulated host systemic inflammatory response to infection. Defense against host infection is the primary role of innate immune cells known as neutrophils. Neutrophils also contribute to host injury during sepsis, making them important potential targets for sepsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 233 publications
(258 reference statements)
0
41
0
2
Order By: Relevance
“…Canine in vivo work indicated that short-term oral resveratrol supplementation resulted in increased phagocytosis by PMNs, blunted oxidative burst capacity, increased PAMP-stimulated TNF and IL-6 production and no effect on IL-10 [34]. It is argued that the preserved effects of PMN phagocytosis and oxidative burst functions represent a desirable outcome in our study as those functions are a critical first line host defense to eliminate pathogens and combat infections [35].…”
Section: Discussionmentioning
confidence: 80%
“…Canine in vivo work indicated that short-term oral resveratrol supplementation resulted in increased phagocytosis by PMNs, blunted oxidative burst capacity, increased PAMP-stimulated TNF and IL-6 production and no effect on IL-10 [34]. It is argued that the preserved effects of PMN phagocytosis and oxidative burst functions represent a desirable outcome in our study as those functions are a critical first line host defense to eliminate pathogens and combat infections [35].…”
Section: Discussionmentioning
confidence: 80%
“…interleukin-6 (IL-6), serum amyloid A (SAA), soluble CD14 (sCD14) and procalcitonin (34,35). Measurement of sCD14 provided contrasting results: no signi cant differences in concentration were recorded among time in experimental settings (34), while sCD14 was higher in in spontaneous clinically endotoxemic than nonendotoxemic horses, showing however no correlation with LPS concentration (36).…”
Section: Resultsmentioning
confidence: 99%
“…However, all the horses had at least 2 alterations of clinical parameters consistent with SIRS status evaluation proposed by Roy et al (32) and therefore it can be assumed that LPS administration induced a systemic in ammatory reaction. Biomarkers of sepsis so far evaluated in horses include interleukin-1β (IL-1β), interleukin-10 (IL-10), interleukin-6 (IL-6), serum amyloid A (SAA), soluble CD14 (sCD14) and procalcitonin (34,35).…”
Section: Discussionmentioning
confidence: 99%